APA HUBUNGAN PANCASILA DAN KEBIJAKAN PUBLIK? - Xaverius Chandra (Arete, 2019)
The quote of Mohammad Hatta’s statement should have triggered Indone- sians to reÀect on whether the Indonesian state was based on Pancasila if the 1945 Constitution was used? If the implementation of the constitution is related to public policy, should public policy in Indonesia be based on Pancasila? What is the basis of the Pancasila underlying public policies in Indonesia? Is that because Pancasila is the basis of the state so that it also underlies public policy in Indone- sia? So, if Pancasila underlies public policy, what does it mean to base it here? Can Pancasila underlie public policy? These are the questions from this essay that were made for the 2018 Faculty of Philosophy Extension Course which raised the theme of general good in relation to public policy. Key Words : Pancasila, Public Policy